Membaca Terminologi Tasawuf Dalam Kitab At-Tafsīr Al-‘Irfānī Li Al-Qur’ān Al-Karīm: Kajian Atas Huruf-Huruf Muqaṭṭa‘āt - Haqqi, Abdul; Zaky Mubarak, Ahmad; Irawan, Bambang (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This study discusses the explanation of the muqaṭṭa‘āt letters found in at-Tafsīr al-‘Irfānī li al-Qur’ān al-Karīm. This work contains a symbolic interpretation of the disconnected letters opening certain surahs, highlighting the richness of the Qur'an's linguistic expression and the depth of meaning it holds. Letters such as alif lām mīm, ṭā hā, and kāf hā yā ‘ain ṣād are understood not merely as meaningless letter combinations, but as containing spiritual and reflective messages that lead to a deeper understanding of the revelation. This research finds that the explanation of the muqaṭṭa‘āt letters in at-Tafsīr al-‘Irfānī emphasizes both linguistic aspects and semantic values that expand the horizons of Qur'anic exegesis. This work serves as evidence that these letters have rhetorical and theological functions in affirming the majesty of the Qur'an. Thus, at-Tafsīr al-‘Irfānī makes an important contribution to the discourse of exegesis by integrating rational explanations and symbolic meanings, opening an interpretive space that is not only textual but also contemplative.